A critical analysis of the role of translation in lexicography with reference to English-Tshivenda bilingual dictionaries - Nthambeleni, Mashudu (University of Limpopo, 2016)
Lack of properly translated Tshivenḓa-English dictionaries is a great challenge to dictionary users. In an attempt to address this challenge or problem, linguistic approach has been employed in this study, which was conducted in Vhembe District in the Limpopo Province, South Africa. This study critically analyses the role of translation in lexicography with special reference to selected Tshivenḓa-/English bilingual dictionaries. The selected dictionaries are: Tshikota’s (2006) Tshivenḓa/English Ṱhalusamaipfi Dictionary and Van Warmelo’s (1989) Venḓa Dictionary. The aim of this study was to examine the role of translation in lexicography with special reference to Tshivenḓa-English dictionaries. This study utilised a qualitative technique to collect the data and interviews were conducted with lexicographers, university lecturers, language practitioners, Tshivenḓa grade 12 educators and court interpreters. Data were analysed based on different answers from different questions posed to different respondents. The study showed that people who compile dictionaries and do translation, do not have proper background in translation. In addition, some of the people are not fluent in both the source and the target languages. It is recommended that in order to produce user-friendly dictionaries, compilers and translators should get a proper training in translation. In addition, translators should be fluent in both the source and target languages. Finally, school books (including prescribed and content books), should be translated in order to provide effective teaching and learning.
Thesis (Ph.D.) --University of Limpopo, 2016.
Keywords: Translation; Lexicography; Bilingual dictionaries; Lexicolography; Language and languages